Why globalization works for America : how nationalist trade policies are destroying our country - Goldberg, Edward (Potomac Books, an imprint of the University of Nebraska Press, 2020)
"In Why Globalization Works for America, the author explains why globalization is here to stay, why America is the winner in the game of globalization, and why all the king's horses and all the king's men can't put the Humpty Dumpty of yesterday's nonglobalized world back together again"--